HIGHER EDUCATION OF LAWYERS: THE CENTRALIZED QUALIFICATION EXAM - Krivins, Anatolijs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The research analyses the current situation of legal education in Latvia, Germany and United Kingdom. The current changes in the Latvian higher legal education system are mainly related to the introduction of the centralized lawyer qualification exam. The research aim is to find out the strengths and weaknesses of the centralized lawyer qualification exam, to offer practical solutions for improving the quality of higher education. The following primary methods have been used in the study: in order to assess the applicability of the new solutions in Latvia, the study analyzed the materials for the development of normative legal acts, opinions of lawyers and scientific literature. A summative content analysis was performed. In addition, the study is based on an analysis of the historical and contemporary experiences of United Kingdom and Germany. As a result of the analysis, it has been concluded that it is necessary to transform legal education programs not only at the master's level, but also at the bachelor's level. The future work will include the implementation of empirical studies in the field of analysis of training programs in Latvia. The research novelty: the research covers the challenges of implementing new measures and assesses the role of different actors in the transformation process.